PENGEMBANGAN INSTRUMEN LITERASI NUMERASI PADA LEVEL PENALARAN DALAM KONTEKS PERSONAL TINGKAT SMP - Kusumo, Bangun Jati; Hepsi Nindiasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study consists of both research and development (R&D) components. Developing a reasoning-level numeracy literacy description test instrument with a personal context for junior high school students is the goal of this research project. Oriondo and Antonio models, as well as the Wilson model, are the research models that are employed. In order to choose the content that will be created into a description test product, the study first establishes learning objectives that are specific to the curriculum. After that, the product is validated by professionals and changed based on their feedback. To produce a legitimate description test product, tests for validity, reliability, difficulty level, and differentiating power are conducted after the questions have been revised. Ultimately, this study yielded four legitimate descriptive questions that might be applied to learning assessments or further research on the topics of mathematical literacy and numeracy skills.